Consumer Purchasing Decisions in Review of Price, Service Quality, and Location at Candaria Kediri Souvenir Shop - Prasetiyo, Nabila Ayu Permatasari; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2025)
Research purposes : This study aims to examine and evaluate consumer purchasing decisions in terms of price, service quality, and location at the Candaria Kediri souvenir shop. Design/Method/Approach: A quantitative descriptive approach is the basis of this research. The population studied were consumers who had made at least one purchase at Toko Oleh-Oleh Candaria Kediri. The number of samples in this study was 40 people. The data source was obtained through a questionnaire distributed to customers of Toko Oleh-Oleh Candaria Kediri. The sample was selected randomly, using a simple random sampling technique, while data analysis was carried out using the multiple linear regression method. Data processing was carried out using SPSS version 25. Research Findings: The results of the study show that price, service quality and location together have a large contribution to the purchasing decisions of consumers who shop at the Candaria Kediri Souvenir Shop. Theoretical contribution/Originality: Simultaneous measurement of price, service quality, and location variables in purchasing decisions. Practical/Policy Implications: Readers should gain deeper insights into how price, service quality, and location influence purchasing decisions, which in turn may enhance firm competitiveness. Research limitations: This study is limited to Candaria Souvenir Shop in Kediri and focuses on the variables of price, service quality, and location. Only consumers who have made at least one purchase participated in this study.